If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -2 = -1x + 9 Reorder the terms: -2 + X = -1x + 9 Reorder the terms: -2 + X = 9 + -1x Solving -2 + X = 9 + -1x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + X = 9 + 2 + -1x Combine like terms: -2 + 2 = 0 0 + X = 9 + 2 + -1x X = 9 + 2 + -1x Combine like terms: 9 + 2 = 11 X = 11 + -1x Simplifying X = 11 + -1x
| 90x+36x= | | N^2-10n+14=-2 | | 2(5y-3)= | | 51.2=x+(-31.3) | | 24y+16y= | | 25+40+x=180 | | -5+4+2x=16 | | x+15=-63.4 | | 9x(4x+7b)= | | (y-1)=-12x | | y^2+1=y+5 | | 2xyz+yz= | | 3.2x^2-16.8x-16.8=0 | | 54.2+x=-45.8 | | 9y^2-81y+1=0 | | x+34.2=67.1 | | 6x+7-2x+4=4(3x-5)-17 | | 9=0.4x-8 | | -81=-92.6+x | | M=2(30)+80 | | 2a^2+2=-7 | | M=2x+80 | | 28y+16z= | | -x+58.1=89 | | x+(-67.1)=54.6 | | 65=-16t^2+vt+s | | x^2-4x-12.8=0 | | 4(3x-1)+10= | | 2lnx=ln(6+x) | | -67.5+x=22.7 | | 6y+18y= | | x+38.6=-82.1 |